2014
DOI: 10.1371/journal.pone.0086219
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Infects Rat Astrocytes but Does Not Affect Their Viability

Abstract: Tick-borne encephalitis virus (TBEV) causes one of the most dangerous human neuroinfections in Europe and Asia. To infect neurons it must cross the blood-brain-barrier (BBB), and presumably also cells adjacent to the BBB, such as astrocytes, the most abundant glial cell type. However, the knowledge about the viral infection of glial cells is fragmental. Here we studied whether TBEV infects rat astrocytes. Rats belong to an animal group serving as a TBEV amplifying host. We employed high resolution quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 64 publications
9
99
3
Order By: Relevance
“…Previous studies have revealed that although TBEV infects astrocytes, viral infection did not affect the viability of the cells [34,35]. Similar findings have been observed with other viral infections such as WNV, JEV, and Junin virus whereas infection with Venezuelan equine encephalitis virus infection induced cell death in cultured astrocytes [31,37,39,85,86].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies have revealed that although TBEV infects astrocytes, viral infection did not affect the viability of the cells [34,35]. Similar findings have been observed with other viral infections such as WNV, JEV, and Junin virus whereas infection with Venezuelan equine encephalitis virus infection induced cell death in cultured astrocytes [31,37,39,85,86].…”
Section: Discussionsupporting
confidence: 77%
“…This indicated that response to type I IFN is more important for restricting viral growth than the basal expression level of antiviral ISGs. Previous studies have shown that astrocytes are resistant to TBEV-induced cytopathic effects [34,35]. We can now show that the viability of WT astrocytes after TBEV infection is dependent on the type 1 IFN response, since IFNAR −/− , as well as WT astrocytes treated with an IFNAR-specific antibody, rendered them susceptible to TBEV-induced cytopathic effect 48 hpi (Fig.…”
Section: Ifn Signaling Restricts Tbev Spread In Astrocytessupporting
confidence: 58%
See 1 more Smart Citation
“…While working with infectious, radiolabeled virus particles may be inconvenient, the use of high MOIs is potentially more problematic, since aggregates of virus particles can influence the apparent mechanisms of viral entry (43). More recently, the entry of individual, fluorescently labeled flavivirus particles has been visualized at low MOIs through live cell imaging (30,(44)(45)(46). An important caveat to this approach is that flavivirus preparations typically have relatively low specific infectivities (44,45,47), so it is difficult to know whether a given particle under observation is on a pathway toward productive infection.…”
Section: Discussionmentioning
confidence: 99%
“…Within the CNS, neurons are the primary target for infection by TBEV and undergo apoptosis (5962). While astrocytes can also become infected, these cells appear to be primarily involved in cytokine production and do not undergo morphological changes or apoptosis (63, 64). We do show that LGTV antigen co-localized to areas of apoptotic cells, and based on previous literature, these infected cells may be primarily neurons and/or neutrophils (35, 5962).…”
Section: Discussionmentioning
confidence: 99%